Writing that sells : persuading others to buy your ideas - Begley, Kathleen A. (Crisp Pub. Menlo ParkUS, 2002)
Applies basic sales principles in presenting strategies for persuasive business writing. Presents the five-step S.A.L.E.S model (Start Add List Evaluate Sign off) for business correspondence that persuades, motivates and influences readers. Provides techniques for appealing to the perceived sensory and personality styles of readers, and includes tips on basic grammar and style in writing.